Novel Osteomyocutaneous Flap Model for Vascularized Composite Allotransplantation - David L. Tran; Michael F. Cassidy; Sachin R. Chinta; Alay R. Shah; Ren-Wen Huang; Eduardo D. Rodriguez; Daniel J. Ceradini (JPRAS Open, 2024)
Background: Vascularized composite allotransplantation (VCA) has become a viable option for restoration of devastating injuries that are not amenable to conventional reconstructive techniques. However, the relative scarcity of procedures performed worldwide, as well as the potential for iatrogenic injury with biopsies, makes studying the immunopathogenesis of acute rejection challenging. Translational VCA research focuses on developing strategies to overcome these barriers with the use of animal models can be technically challenging and difficult to replicate without highly trained microsurgeons. Methods: We describe a modified model of a femur-based composite tissue allograft using an adapted vascular cuff anastomotic technique with a tunneled skin flap in a rodent model. Results: The use of a heterotopic osteomyocutaneous flap with a subcutaneously tunneled-skin paddle to the posterolateral aspect of the recipient rodent allows for ease of flap monitoring and reduces the risk of self-mutilation. A total of six transplantations were conducted with no signs of self-mutilation. Operative time decreased as our surgical technique improved, and long-term graft tolerance was possible under our immunosuppressive regimen. Additionally, we demonstrate cases of successful transplantation in both an allogeneic and syngeneic rodent model. Conclusion: Animal models, although technically challenging, are a reliable and reproducible modality that has been used to investigate various aspects of VCA immunology. We describe the success of an osteomyocutaneous flap with a modified vascular cuff anastomosis that can be used by investigators with less experience in microsurgical techniques to further our understanding of VCA physiology. Furthermore, tunneling of the skin paddle reduces the risk of self-mutilation and other external factors affecting the graft.